THE EFFECT OF NANOCHITOSAN FROM RHINOCEROS BEETLE (Xylotrupes gideon) TOWARDS GIC SURFACE ROUGHNESS ON CRITICAL pH OF THE SALIVA - Deviyanti Pratiwi; Gabriel Rainheart Genesis; Komariah Komariah; Rosalina Tjandrawinata (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Xylotrupes gideon is a harmful insect because it damages the shoots of coconut trees. Xylotrupes gideon has begun to be used in the form of nanochitosan as an alternative in dentistry. The addition of nanochitosan to Glass Ionomer Cement (GIC) material is a modification to improve the properties of GIC, such as surface roughness caused by acidic conditions (critical saliva pH). Nano-sized chitosan is able to increase stability and better absorption, thus inhibit demineralization and increase tooth hardness. This research aimed to investigate the effect of nanochitosan from Xylotrupes gideon on the surface roughness of GIC at critical saliva pH.Method: This research type conducted is an experimental laboratory. Samples of 10 mm (height) x 2 mm (diameter) divided into 2 groups, (A) Unmodified GIC (control group), (B) GIC modified with 10% nanochitosan solution. Samples of the treatment and control group are stored in the incubator at 370C for 1 hour before early surface roughness testing and continued in critical saliva pH (5,5) for 7 days in the incubator before the final test. The surface roughness tester using sutrotonic s-100 series.Result: There was an increase in the surface roughness of conventional GIC by 0.133 µm and GIC nanochitosan by 0.122 µm. The results of the paired t-test before and after immersion in the two groups showed that there was a significant difference (p <0.05) between conventional GIC and nanochitosan GIC. The independent t-test results showed that there was no significant difference (p> 0.05) between the nanochitosan GIC and conventional GIC.Conclusion: Nanochitosan can reduce the surface roughness value of GIC at critical saliva pH, although there is no significant difference to conventional GIC.